On Lorentzian Sasakian Manifolds (Global Journal of Science Frontier Research, 2020)
The object of this paper to study various curvature tensors in a Lorentzian Sasakian manifold, we also study pseudo projectively flat,quasi conformally flat, quasi concircularly flat, projectively flat Lorentzian Sasakian manifolds are an Einstein Manifold.
Keywords: pseudo projectively flat; quasi conformally flat; quasi concircularly flat